In-situ coagulation moulding of ceramic suspensions - J.G.P. Binner; A.M. McDermott; Y. Yin (2004)
A fast, near-net shape route for the production of advanced ceramic components has been developed in which the time dependent in-situ hydrolysis of carboxylic acid derivatives progressively destabilises a suspension within a non porous mould to form a viscoelastic green body solid within which the homogeneity of the initial dispersion is maintained. After drying, the ceramics could be sintered without needing debinding since